Alfred Martin Duggan-Cronin's photographs for The Bantu Tribes of South Africa (1928-1954): The construction of an ambiguous idyll - Godby, Michael (Kronos: Southern African Histories, 2017)
The collection of A.M. Duggan-Cronin photographs at the University of Cape Town has experienced mixed fortunes since it was acquired some seventy years ago, being displayed proudly at one moment and stowed away in embarrassment at the next, only to be exhibited again for some new purpose. This paper looks at the original context of Duggan-Cronin's The Bantu Tribes of South Africa in political, anthropological and aesthetic terms; and it examines the first volume on The Bavenda (1928) in some detail. The paper argues that Duggan-Cronin may be shown to have constructed his photographs of African subjects in certain ways apparently to create a specific image of Africa that had obvious political connotations. This primitivising image made a forceful contribution to the 'Native Question', which was the most important single issue of South African politics of the mid-twentieth century. However, given the openness of visual communication, on the one hand, and change in political circumstances, on the other, the Duggan-Cronin photographs show that, over time, the same image can serve apparently quite contradictory purposes.